Exploring agency and entrainment in joint music-making through the reported experiences of students and teachers - Stolp, Eveliina; Moate, Josephine; Saarikallio, Suvi; Pakarinen, Eija; Lerkkanen, Marja-Kristiina (Frontiers in Psychology, 2022)
This qualitative interview-based study draws on the reported experiences of students and teachers to explore how agency and entrainment resource and constrain each other in joint music-making. The participants were 23 students of Grades 6 and 11 music teachers from different primary schools. The qualitative content analysis of the 11 student pair interviews and 11 one-to-one teacher interviews indicated that experiences of music-related interpersonal entrainment intertwine with different dimensions of agency. In the analysis, four themes were identified as follows: presence, belonging, safety, and continuity. These findings provide insights into the relationship between agency and entrainment in classroom-based joint music-making and provide a novel lens through which to examine the complementary experiences of students and teachers. This study builds bridges between the concepts of agency and entrainment in the context of music education, offering theoretical clarification as to how and why joint music-making can be considered an intersubjective activity that fosters group cohesion and social interaction. The findings further present a view of the constitutive nature of the relationship among agency, entrainment, and intersubjectivity in joint music-making. The findings offer educators concrete grounds for using joint music-making as a platform for an agency.